Determination of Factors Affecting the Concentration of lead and cadmium in Wheat and Some of its Products (Damascus University Journal of agriculture sciences, 2024)
This study aimed to conduct a survey to determine the degree of contamination of heavy metals (lead and cadmium) in different samples of local and imported wheat grains (local durum wheat, local bread wheat and Russian imported soft wheat prepared for milling), samples of flour types (high quality flour and standard flour) and bran, from different sources of wheat and in different seasons. These samples were collected from a number of county mills during two seasons (Spring and Autumn) during 2018. The concentration of lead and cadmium were measured by atomic absorption in laboratories of Soil Science Department, Faculty of Agriculture, University of Damascus. The results revealed that the concentration of lead in wheat grain samples exceeded the maximum allowable concentration of food (0.200 mg/kg) and reached very high concentrations (1.477 mg/kg). By contrast, the percentage of cadmium contamination was below the maximum allowable concentration in food (0.050 mg/kg). The source of wheat had a significant effect on the variation in cadmium and lead ratios in the wheat grain samples. These results revealed the importance of the area planted with wheat on the degree of contamination of wheat grains with these minerals. On the other hand, the concentration of lead in the flour samples were lower compared to the grain samples, while the samples of flour produced in Spring only showed values higher than the permitted concentrations of cadmium. The mill and the flour type showed a significant effect on the degree of contamination of the flour by lead, while the mill and the season had the greatest effect on the degree of contamination by cadmium. All bran samples showed concentration of lead higher than (0.200 mg/kg) and values of cadmium concentration lower than (0.050 mg/kg). The mill had a strong controlling effect on the degree of lead contamination of the bran, while the season had the greatest effect on cadmium.
Keywords: Wheat Kernels; Flour; Bran; Lead; Cadmium